The Role of the European Union in Conflict Resolution in Africa: Towards Comprehensive, Integrated and Long-Term Commitment? - Forysiński, Wojciech (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
The overall aim of this article is to provide an insight into EU’s engagement and increasing role in conflict resolution in Africa. The question addressed in this article is about the nature and scope of this commitment. To that end, this article provides an up-to-date analysis of the instru¬ments committing the European Union to conflict resolution in Africa with a view to define and delimit, contextualize and measure its normative density. It takes a closer look at both unilateral instruments of the EU as well as those originating from the Union’s contractual relations with its African partners. It addresses a number of controversies generated by the normative: vertical and horizontal, institutional and functional fragmentation of the EU’s commitment to conflict resolu¬tion in Africa. The overarching argument presented in this article is that the European Union and its African partners need to move away from their dramatically fragmented partnership toward a more comprehensive, integrated and long-term regime for the EU’s engagement in conflict res¬olution in Africa.

Zasadniczym celem tego artykułu jest problemowe przedstawienie coraz głębszego zaangażowania Unii Europejskiej w rozwiązywanie konfliktów w Afryce. Opracowanie koncentruje się na badaniu charakteru i zakresu tego zaangażowania. W tym celu autor podejmuje analizę wybranych dokumentów unijnych i umów międzynarodowych zawartych przez Unie z jej afrykańskimi partnerami, które zobowiązują Unię Europejską do współdziałania przy rozwiązywaniu konfliktów w Afryce. Autor koncentruje się także na kwestii fragmentacji zobowiązań UE do działania w Afryce, uwypukla jej najistotniejsze elementy i wynikające z niej konsekwencje. W artykule zasugerowano, iż niezbędne jest podjecie kroków w celu ograniczenia negatywnych skutków fragmentacji oraz, ze spójność unijnych zobowiązań w tym zakresie pozwoliłaby na uporządkowanie reżimu prawnego i wzmocnienie działań Unii Europejskiej i jej państw członkowskich w Afryce.
Rola Unii Europejskiej w rozwiązywaniu konfliktów w Afryce - w kierunku pełnego, zintegrowanego i długoterminowego zaangażowania?